Genetic Literacy for Students in Faculties of Education in Universities - Ali Raheem Mohammed; Raheemah Rwayyih Habeeb; Nibal Abbas Hadi Al-Muhja (Jurnal VARIDIKA, 2022)
Genetic literacy is the capacity to obtain, process, understand, and use genetic information. It is highly imperative in life science students; the current study was conducted to assess genetic literacy in students. The goals of the current project are (1) to assess the Genetic Literacy of life sciences students in education colleges, and (2) to identify how Genetic Literacy changes according to variables of academic level, gender, and different universities in education students in universities of the Furat Al-Awsat. To achieve the project's goals, the two researchers used the analytical-descriptive method using the steps such as an examination prepared to assess the impact of the variables of interest. Experts then reviewed it to confirm its legitimacy, clarity, and suitability to the target audience. The testing timing was then inferred using a trial on a sample consisting of 40 students that belong to the target audience. The test was then applied to a sample of 395 students in the second semester of the academic year 2020-2021. The sample was randomly selected from the universities of Al-Qādisiyyah, Karbala, and Kufa. The statistical packages, SPSS-26, and Microsoft tool, Microsoft Excel, were used to process the collected data and show that education-department students of the selected universities did not possess Genetic Literacy. Varying gender did not have a statistically clear impact on Genetic Literacy. Differences in genetic literacy were identified between 3rd and 4th-level students and their 1st and 2nd counterparts. The researchers concluded the necessity of integration among the contents of education and genetic literacy applied to the size, type, and quality of the material and activities in the curriculum. They also suggested that further studies must be made to study the relationship between students' level of genetic literacy and that of educators.